Trans‐Stilbene epoxidation by He+O2 atmospheric pressure plasma: Epoxidation without oxidant waste stream. Issue 1 (2nd October 2019) - Xu, Han; Wang, Sui; Shaban, Muhammad; Montazersadgh, Faraz; Alkayal, Anas; Liu, Dingxin; Kong, Michael G.; Buckley, Benjamin R.; Iza, Felipe
Abstract: Plasmas interacting with organic liquids can lead to novel synthetic processes that are not feasible with conventional vacuum systems due to vapor pressure limitations. Of particular interest are processes that eliminate the generation of waste streams. Here, we show that He+O2 plasma can drive the epoxidation of alkenes in solution, in a process that generates epoxides without oxidant waste streams, runs at room temperature and atmospheric pressure, and requires no catalyst. The reactions between different reactive oxygen species generated in the plasma and the target alkene, trans ‐stilbene in this study, have been identified and optimization of the plasma conditions within the constraints of the current experimental setup has led to yields of ~70%, which are of preparative interest. Abstract : He+O2 atmospheric pressure plasmas can drive the epoxidation of alkenes in solution, in a process that generates epoxides with yields of up to ~70% at room temperature and atmospheric pressure, without the need for catalyst and without generating oxidant waste streams.